Experimental characterization of the complete life cycle of Haemoproteus columbae, with a description of a natural host-parasite system used to study this infection. Issue 12 (November 2019) - Cepeda, Axl S.; Lotta-Arévalo, Ingrid A.; Pinto-Osorio, David F.; Macías-Zacipa, Jhon; Valkiūnas, Gediminas; Barato, Paola; Matta, Nubia E.
Graphical abstract: Highlights: An experimental model system for following Haemoproteus infection was established. The complete life cycle of Haemoproteus columbae was investigated experimentally. Merogony and parasitaemia during H. columbae infection are described. We present new experimental data on sporogonic development of H. columbae . Abstract: Characterization of complete life cycles of haemoparasites requires the maintenance of suitable susceptible vertebrate hosts and vectors for long periods in captivity, in order to follow the complete parasitic cycle in definitive and intermediate hosts. Currently, there are few host-parasite models established in avian haemosporidian research, and those have been developed mainly for species of Passeriformes and their parasites. This study aimed to develop an experimental methodology to access the complete life cycle of Haemoproteus columbae ( cytb lineage HAECOL1), which parasitizes the Rock Pigeon ( Columba livia ) and louse fly ( Pseudolynchia canariensis ). A colony of louse flies, which are the natural vectors of this parasite, was established. Thirty newly emerged insects were exposed to H. columbae infection and used to infect naïve Rock Pigeons. The peak of parasitaemia (acute stage) was seen between 27 and 32 days p.i. when up to 70.8% of red blood cells were infected. The crisis occurred approximately 1 week after the peak, and the long-lasting chronic parasitaemia stage followed. Exo-erythrocytic meronts were seen mainly in the lungs where extensive tissue damage was reported, but also in the kidneys and spleen. In the vector, the sporogonic cycle of H. columbae was completed between 13 and 16 days p.i., at an average temperature ranging between 12 and 15 °C. This host-parasite model is tractable for maintenance in captivity. It is recommended for use in studies aiming for detailed characterization of host-parasite relationships in areas such as physiology, pathology, immunobiology, genetics, as well as for evaluative treatments and to follow the infection in any stage of parasite development both in the vertebrate or invertebrate host.